2022
DOI: 10.3390/polym14112223
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dental Pulp Stem Cells Response to Bone Substitutes Biomaterials in Dentistry

Abstract: Bone substitute biomaterials (BSBs) represent a promising alternative to bone autografts, due to their biocompatibility, osteoconduction, slow resorption rates, and the ability to define and maintain volume for bone gain in dentistry. Many biomaterials are tailored to provide structural and biological support for bone regeneration, and allow the migration of bone-forming cells into the bone defect. Neural crest-derived stem cells isolated from human dental pulp (hDPSCs) represent a suitable stem cell source to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The study reported that the three biomaterials were biocompatible. Interestingly, when hDPSCs were incubated with the collagenated GTO and Gen-Os, an induction of intracellular osteopontin and an enhanced alkaline phosphatase activity were observed, suggesting that these materials contribute to the osteogenic commitment of these cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that the three biomaterials were biocompatible. Interestingly, when hDPSCs were incubated with the collagenated GTO and Gen-Os, an induction of intracellular osteopontin and an enhanced alkaline phosphatase activity were observed, suggesting that these materials contribute to the osteogenic commitment of these cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…An animal study revealed that Angelus MTA upregulated the adaptive immune response but had minimal or no impact on the production of pro- or anti-inflammatory cytokines [ 109 , 110 ]. Another study conducted by Rosanna et al [ 16 ] underscores, that hDPSCs exposed to the three different bone substitute biomaterials such as OsteoBiol® GTO® [ 111 ], OsteoBiol® Gen-Os® [ [112] , [113] , [114] ], and OsteoBiol® Apatos® [ 115 , 116 ], promote both osteoblast and osteoclast activity. This finding highlights hDPSCs as a suitable stem cell source for investigating the effects of various biomaterials [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These distinctive characteristics position hDPSCs as a promising cell line for regenerative dentistry [ 3 , 4 , 8 , 11 , 14 , 15 ]. The hDPSCs are a suitable stem cell source for studying biological properties, suggesting their versatile suitability to different dentistry applications [ [16] , [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%